STRATEGI MEMPROMOSIKAN INFORMASI HASIL PENELITIAN: STUDI PADA PUSAT DOKUMENTASI DAN INFORMASI ILMIAH LEMBAGA ILMU PENGETAHUAN INDONESIA - Suryati, Yati; Lukman, Eduard (BACA: Jurnal Dokumentasi dan Informasi, 2017)
Center for Scientific Documentation and Information of Indonesian Institute of Sciences has already created a platform system which is intended to facilitate people in accessing and obtaining the scientific information. The institution promotes platform services which enable people to easily find the scientific information required for their research paper. This study aims at analyzing the corporate promotional communication strategies. Researchers use eight effective promotional communication elements which consist of identifying the targeted audience, determining the communication objectives, designing the messages, selecting the channels, budgeting, deciding promotional tools, measuring the results, managing and coordinating the integrated marketing communications. This research is a single case study which data are collected from in-depth interviews, and documentation studies. The results show that the promotional communication strategies have already fulfilled seven of eight effective promotion communication elements although it is still not optimal yet. The element which has not been fulfilled is on measuring the promotional results. Cost budgeting is one element which also requires to be optimized more. It would be better if the institution uses objective and task method to clearly define the specific objectives and determine the required tasks to perform in achieving those objectives as well as to estimate costs in performing those tasks. By implementing these methods, it is expected that the short-term and long-term goals may be clearly defined that the goals of the promotional activities may be achieved better. In addition, the team formation focusing on the promotional activities may also become a consideration for the effectively and efficiently integrated marketing and promotional communication.